Stability testing of oil-in-water emulsion of Syzygium aromaticum (clove) - Abdul Ghafar, Syafiq; Yusof, Fathin Athirah; Mohd Shafri, Mohd Affendi (Scigen Publisher (Regd.), 2015)
Extract of Syzygium aromaticum (Clove) is a lipophilic substance with low solubility in aqueous solution. As this may compromise its handling, bioavailability, and bio-absorption, oil-in-water (O/W) emulsion is formulated. Briefly, dried flower buds of cloves were grounded into a fine dry powder and macerated in absolute ethanol solvent for 48 h duration with intermittent shaking at the room temperature. The extracts of the cloves were filtered before being evaporated by a rotary evaporation method (200-75 Mbar; 60°C, 90 rpm) in order to isolate the solvent from the extracts. An O/W emulsion system was prepared by mixing various surfactants (Tween 80, Tween 20, and Span 20) to emulsify the clove oil in the aqueous phase. Initial screening was done on the prepared formulations with centrifugation (3000 rpm, 3 min) to detect for any phase separation in these formulations. The most stable formulation of O/W emulsion of the cloves (no phase separation) which consisted of 34.48% distilled water (aqueous phase), 34.48% clove oil (oil phase), 27.59% Tween 20 (surfactant), and 3.45% Tween 80 (surfactant) were tested for its stability at different storage conditions (8°C [in refrigerator], 25°C [in temperature controlled room], and 40°C [in oven]) at different time points (24 h, 48 h and 72 h). Stability evaluation consists of organoleptic characteristics, centrifugation tests, particle size measurements, microscopic observation, pH determination, and freeze thaw cycle tests. Results showed that the O/W emulsions samples kept at 8°C displayed good stability over 72 h of observation period and could be used for tests in which stability, ease of handling, and improved pharmaceutical characteristics are of importance.